Population as a system in regional development - Alonso, William (American Economic Review, 1980)
Or to put it another way in this simple model the wage difference would have to rise over time to produce a constant rate of net immigration. This example of a negative feedback within the population system well documented in the economic and sociological migration literature has been amply ignored in the literature of urban and regional economics although migration has been the demographic process treated as endogenous in this literature. Fertility processes which are especially important for long-run analysis have been ignored or treated shallowly as exogenous in urban and regional economies. The balance of this paper will refer to some of the complexities of these processes. (excerpt)